Student leadership as indicator of active citizenship in New Lucena, Iloilo - Abolar-Sustento, Mylene (University of the Philippines Visayas, 2019)
The study on "Student Leadership as Indicator of Active Citizenship in New Lucena, Iloilo" specifically aims to determine the types of student leadership practices in New Lucena National High School in SY 2017-2018, enumerate the various tasks and activities of the different student leaders for SY 2017-2018 and analyze the connections between student activities in school and the practice of active citizenship in the community. Six (6) student leaders fron New Lucena National High school were respondents who were selected through purposive sampling. Individual interviews of the respondents were conducted using guide questions which has two components namely, student leadership and community involvement. Thematic analysis of the data derived from the answers of the respondents was used to achieve the aims of the study. Student leadership i New Lucena National High School s leading toward students' participation, development, protection and survival. Through their involvement in student leadership, they experienced democratic action, distributive leadership, discipline, social responsibility, role modelling, conflict management and respect of diversity which were considered as constructs of leadership. Various tasks and activities of student leaders are conducted inside the campus and outside the school. Student leaders are voluntarily involved in the community activities such as: driving problems of the community, support programs of the community, represents the community,initiating educational program, and through participation in dialogue and discussion. Different opportunities are derived from student leadership, making them competent or developing them to become active members of the community. Student leadership involvements that were extended in the community are proofs of the application of their learnings and skills which were obtained from being student leaders in school.